The Analysis of the Legal Protection of Ship's Crew in Sea Work Agreement in Indonesia - Putra, Tegar Islami (Indonesian Journal of Advocacy and Legal Services, 2023)
This article aims to analyze the welfare of crew members in the context of legal protection, which is reviewed in more detail from the perspective of the implementation of the maritime employment agreement in Indonesia. This is based on the poor execution of marine employment agreements in Indonesia and should pay more attention to the welfare of crew members. This research will be prepared using normative juridical research (legal research), which is research focused on examining the application of rules or norms in positive law in Indonesia. The assessment process is carried out by analyzing several related regulations, namely the Commercial Code, Laws, Government Regulations, and Ministerial Regulations. The results show that the implementation of sea work agreements in Indonesia involves various parties, such as employers/ship agents, skippers, crew members, and harbourmaster as a means of fulfilling the rights and obligations of workers and employers. In the context of legal protection, crew members in Indonesia have the right to work protection in the form of welfare, occupational safety, and occupational health. In addition, crew members also have the right to salary, overtime pay, holiday pay, delegation pay, transportation costs and wages at the end of work in a sea work agreement.